Physical and expert investigation of the Islamic garden design and principles for Malaysia - Abdul Latiff, Zainab (2017)
There is a long tradition within the Muslim community of creating gardens. The gardens, from its starting period, had always functioned to provide shade, serenity and the feel of relaxation from the stresses of daily life. Even though Islamic gardens have fascinated designers, landscape architects, architects and historians since the fourteenth century, their evolution throughout time has gone through a continuous phase of numerous definitions, interpretations, descriptions and representations that led to uncertainty more than clarity. The continuous phase of numerous interpretations of Islamic garden by the Western and Muslim scholars makes its definition remained unclear. Without a detailed understanding of its true definition a framework for Islamic garden design cannot be established. This framework is pertinent to guide designers and professionals in developing an Islamic garden that suits the current society’s needs in particular and the future community as a whole. The objective of this study is to establish a framework of Islamic garden design for Malaysia. This research uses a qualitative approach for its data collection through library search, Interactive Focus Group (IFG) discussion and semi-structured interviews. The framework of Islamic garden design for Malaysia is inspired primarily by Islam, permeated with the theory of Islamic arts and principles, and stands for the embodiment of Islamic values. It emphasizes the Islamic principles of Oneness of God, beauty, peaceful co-existence with nature, the purpose of man’s creation on earth, balance of creation, embellishment of faith, dynamism of ‘ibadah (subservience), temporality of creation and being charitable. These principles are to be translated into its design elements of contextual setting, layout, built structures, water, vegetation, materials, ornaments and fauna thus to be an ethically-disciplined vision through intelligent contemplation by its designers and the users.